Activities that early care educators are implementing in their childcare environments during the COVID-19 era - Obeng, Cecilia; Obeng-Gyasi, Emmanuel (Frontiers in Education, 2023)
Background: Teaching children about healthy lifestyles in early care settings can contribute to children’s optimal health during the COVID-19 era; this is because children are vulnerable to communicable diseases in such settings. This study aimed to discover the activities that early care educators are implementing in their childcare settings to assist children become healthy in the COVID- 19 era. Methods: An open-ended survey was sent to early care providers through anonymous links. The requirement for participation was being an adult aged 18+ years and an educator in early care settings. Responses from Forty-five female educators (n=45) were received, and those of three participants were excluded because of not responding to any of the main questions. A Constant Comparative approach was used to categorize and organize participants’ narratives into themes. Results: Thirty-four out of the forty-two participants indicated that they did activities on hand washing and how to use hand sanitizer. Some participants indicated that hand washing increased in their childcare settings. Others did some of their instructional activities such as reading, painting, and eating snacks outside the classrooms. Participants indicated that they walked around their childcare with children several times for children to get fresh air outside. There were others who canceled extracurricular activities at the height of the COVID-19 pandemic. Others did not do any extra activities in their childcare settings during the COVID-19 era. Conclusion: This study revealed teaching and related activities undertaken by the studied early care educators during COVID-19. It is recommended that higher education professors who train early care educators’ work with them to come up with health education activities that can help children obtain much-needed health knowledge and skills to ensure children’s optimal health during the COVID-19 era.